Cost and Time Control Analysis with Earned Value Method in the MRT-Hub Building Construction - Arifin, Muhammad Faizal Ardhiansyah; Sarifatuzzuhriyah, Maulidiya; Liu, Shu Sun (Universitas Negeri Semarang, 2023)
Along with Indonesia's economy and population growth, the community's need for building construction and infrastructure will also increase. Project implementation is undoubtedly expected to meet the predetermined quality, time, and cost targets, so a good project management system is needed. However, there is often a mismatch between planning time and realization due to obstacles during project performance, causing delays and over-budget on the project completion. Therefore, it is necessary to monitor the cost and time carried out in an integrated manner to estimate the total cost and time needed until the project is completed. This monitoring is used to avoid delays and cost overruns, which can be done using the Earned Value Analysis Method. This research is expected to monitor and control the time and cost required to implement the MRT-Hub Building Construction Project of Dukuh Atas Intersection to avoid losses or delays when the project is completed. The results of the analysis, based on the Earned Value Analysis Method at week 57th after the addendum, the result of the Schedule Variance (SV) is negative. In contrast, the Cost Variance (CV) is positive (+). The result of the Schedule Performance Index (SPI) is smaller than 1, while the Cost Performance Index (CPI) is greater than 1 ( 1). Thus, it is known that the project performance is running slower than the planned schedule, and the actual cost is smaller than the budget performed. Based on these results, the estimated temporary schedule (ETS) at week 57th is 188.3538 days with a remaining cost (ETC) of IDR 97,526,302,702.70. Meanwhile, the estimated project completion time (EAS) is 584.3538 days with an estimated all-cost (EAC) of IDR 171,868,372,084.14. Thus, it can be concluded that the project is expected to be -0.0606% later than the addendum schedule, with an estimated project profit of 10.0123% of the addendum budget.